2004
DOI: 10.1080/13803390490515522
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Constructional and Visuospatial Abilities in Normal Subjects and in Focal Brain-damaged Patients

Abstract: We tested 125 normal subjects and 24 right and 22 left focal brain-damaged patients (RBD and LBD) on the Rey figure copying test and on a battery of perceptual and representational visuospatial tasks, in search of relationships between constructional and visuospatial abilities. Selected RBD and LBD were not affected by severe aphasia, unilateral spatial neglect or general intellectual defects. Both RBD and LBD showed defective performances on the constructional task with respect to normal subjects. As regards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 24 publications
4
21
1
1
Order By: Relevance
“…performed in the normal range, meaning that his semantic knowledge about famous people was at least relatively preserved. Grossi, 1993;Grossi and Trojano, 1999;Grossi et al, 2002;Trojano et al, 2004), exploring perceptual and representational visuospatial abilities, G.S.' scores were well within the normal control range according to published norms on tasks assessing discrimination of line length and orientation, coding of relative position of points within squares, mental rotation, and analysis and recognition of complex abstract figures (Table 3).…”
Section: Case Reportmentioning
confidence: 85%
“…performed in the normal range, meaning that his semantic knowledge about famous people was at least relatively preserved. Grossi, 1993;Grossi and Trojano, 1999;Grossi et al, 2002;Trojano et al, 2004), exploring perceptual and representational visuospatial abilities, G.S.' scores were well within the normal control range according to published norms on tasks assessing discrimination of line length and orientation, coding of relative position of points within squares, mental rotation, and analysis and recognition of complex abstract figures (Table 3).…”
Section: Case Reportmentioning
confidence: 85%
“…Then, prompted by a first systematic survey about the relationships between visuoconstructive disabilities and hemispheric locus of lesion [12], several authors attempted to ascertain whether qualitative differences existed between the drawing disorders resulting from right or left hemispheric lesions. On one hand, correlational studies demonstrated that drawing disabilities are tightly related with scores on visual-perceptual tasks in right but not in left brain-damaged patients, e.g., [3,4,18,33]. On the other hand, drawing disorders in left-brain damaged patients have been ascribed to a planning disorder [6,7], but this interpretation has not been supported by several empirical studies [8,9,17,18,33].…”
Section: Neural and Cognitive Bases Of Drawingmentioning
confidence: 93%
“…Particularly crucial in this respect seem to be visuospatial perception whose different aspects can be impaired in dementia [44,[75][76][77][78]. Visuospatial perception is often assessed by tests such as Benton's Judgement of Line Orientation, in which subjects are required to identify the lines that have the same angulation as those presented as stimuli [79], or by comprehensive test batteries assessing several aspects of visuoperceptual processing, such as Warrington and James' Visual Object and Space Perception Battery [80], or the Battery for Visuospatial Abilities [4,81]. The mechanisms underlying drawing disorders can also be clarified by means of planning/executive tests, such as Trail Making test [82] or tests for figural fluency [83], and other tests that have been used to assess patients with focal lesions.…”
Section: Drawing Tasks Frequently Used In Dementiamentioning
confidence: 99%
See 1 more Smart Citation
“…Such deficits are typically observed in patients with focal brain lesions [39], but they can also be present in patients with neurodegenerative conditions, such as AD [24,25,42,43] or frontotemporal dementia [23]. Despite its precise anatomical-functional localization being still under debate [24,25,41,44,45], constructional apraxia is generally observed in patients with parietal [39] or frontal lobe [23] damages. For example, in a previous volumetric study we found grey matter atrophy restricted in the parietal, occipital and temporal brain areas of patients with AD and evidence of constructional apraxia [4].…”
Section: Discussionmentioning
confidence: 99%